1987
DOI: 10.1002/job.4030080205
|View full text |Cite
|
Sign up to set email alerts
|

Individual demographic differences and job satisfaction

Abstract: Empirical research and theoretical literature support the notion that demographic differences among employees are associated with job satisfaction. However, the evidence is inconsistent, and little is known about the stability of many of the reported relationships. A meta-analysis was conducted involving 21 independent studies and over 10,000 employees to discern selected population relationships. Results indicated that, with the exception of age and organizational tenure, associations do not differ significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
2
9

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(88 citation statements)
references
References 53 publications
8
68
2
9
Order By: Relevance
“…Even though this relationship was revealed in most studies, the strength of the relationship was weak, with correlations falling between 0.10 and 0.20. Brush, Moch, and Pooyan (1987) conducted a meta-analysis in an attempt to estimate the population parameter representing the relationship between age and levels of job satisfaction. The results showed a mean correlation coefficient of 0.22 for the association between age and job satisfaction.…”
Section: Age and Job Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though this relationship was revealed in most studies, the strength of the relationship was weak, with correlations falling between 0.10 and 0.20. Brush, Moch, and Pooyan (1987) conducted a meta-analysis in an attempt to estimate the population parameter representing the relationship between age and levels of job satisfaction. The results showed a mean correlation coefficient of 0.22 for the association between age and job satisfaction.…”
Section: Age and Job Satisfactionmentioning
confidence: 99%
“…Conversely, the results of the two studies contradict each other by finding differing strengths of the relationship. While Brush et at., (1987) found a moderate relationship (r = 0.22), Sterns (1995) results showed a much weaker association (r = 0.07).…”
Section: Age and Job Satisfactionmentioning
confidence: 99%
“…Bernal, Snyder, and McDaniel (1998) found that job satisfaction increased for both males and females as they got older. Brush, Moch, and Pooyan (1987) conducted a meta-analysis of several studies and found that overall job satisfaction was positively correlated with an increase in age. Other research has shown that job satisfaction varies with age.…”
Section: Agementioning
confidence: 99%
“…This research is in parallel with our findings. Loscocco (1990), Ozdevecioglu (2003 and Brush et al (1987) found out important correlation between gender and job satisfaction. Keser (2006) found out high correlation between gender and job satisfaction from his research with call center workers.…”
Section: Discussionmentioning
confidence: 97%